ANALISIS PENGEMBANGAN KURIKULUM SMK NEGERI 1 ENAM LINGKUNG - Netty Anggraini; Nurhizrah Gitituati; Alwen Bentri (LPPM Universitas Ekasakti, 2024)
The importance of education in developing human potential, improving careers, and helping realize dreams. Education is considered the foundation of culture and civilization, with the curriculum as an integral guide in the implementation of education. The curriculum is considered as a tool to achieve educational goals and determine the direction of the nation's life. Education in Indonesia receives special attention, as stated in the Preamble to the 1945 Constitution.Various efforts, such as the allocation of funds to improve the quality of education, scholarships for students and teaching staff, as well as the